Oropharyngeal and intestinal concentrations of opportunistic pathogens are independently associated with death of SARS-CoV-2 critically ill adults - Juliette Patrier; Khanh Villageois-Tran; Piotr Szychowiak; Stéphane Ruckly; Rémi Gschwind; Paul-Henri Wicky; Signara Gueye; Laurence Armand-Lefevre; Mehdi Marzouk; Romain Sonneville; Lila Bouadma; Marie Petitjean; et al. (Critical Care, 2022)
Abstract Background The composition of the digestive microbiota may be associated with outcome and infections in patients admitted to the intensive care unit (ICU). The dominance by opportunistic pathogens (such as Enterococcus) has been associated with death. However, whether this association remains all throughout the hospitalization are lacking. Methods We performed a single-center observational prospective cohort study in critically ill patients admitted with severe SARS-CoV-2 infection. Oropharyngeal and rectal swabs were collected at admission and then twice weekly until discharge or death. Quantitative cultures for opportunistic pathogens were performed on oropharyngeal and rectal swabs. The composition of the intestinal microbiota was assessed by 16S rDNA sequencing. Oropharyngeal and intestinal concentrations of opportunistic pathogens, intestinal richness and diversity were entered into a multivariable Cox model as time-dependent covariates. The primary outcome was death at day 90. Results From March to September 2020, 95 patients (765 samples) were included. The Simplified Acute Physiology Score 2 (SAPS 2) at admission was 33 [24; 50] and a Sequential Organ Failure Assessment score (SOFA score) at 6 [4; 8]. Day 90 all-cause mortality was 44.2% (42/95). We observed that the oropharyngeal and rectal concentrations of Enterococcus spp., Staphylococcus aureus and Candida spp. were associated with a higher risk of death. This association remained significant after adjustment for prognostic covariates (age, chronic disease, daily antimicrobial agent use and daily SOFA score). A one-log increase in Enterococcus spp., S. aureus and Candida spp. in oropharyngeal or rectal swabs was associated with a 17% or greater increase in the risk of death. Conclusion We found that elevated oropharyngeal/intestinal Enterococcus spp. S. aureus and Candida spp. concentrations, assessed by culture, are associated with mortality, independent of age, organ failure, and antibiotic therapy, opening prospects for simple and inexpensive microbiota-based markers for the prognosis of critically ill SARS-CoV-2 patients.